Efektivitas Hukum Humaniter Internasional dalam Kekerasan Seksual Pada Perang Bosnia Herzegovina - Raden Maulana Hutomo; Marten Hanura (Journal of International Relations Diponegoro, 2021)
Every country has the right to use its military power, however, there are rules in conducting wars for humanitarian reasons. As a result of the war that occurred, there was often sexual violence against women. This happened in the Bosnia-Herzegovina War. However, there are rules that regulate how to go to war by prioritizing humanitarian reasons, which are contained in International Humanitarian Law which is contained in the 1949 Geneva Conventions. Sexual violence that occurs in war is very clear if it violates International Humanitarian Law. Therefore, the author in this study aims to see the effectiveness of existing International Humanitarian Law in reducing acts of sexual violence in war. The author uses the concept of regime effectiveness, which has several indicators in assessing whether the existing regime can be said to be effective or not. The results of this study indicate that actors who are at war have not carried out the right way of fighting even though they have made efforts to reduce sexual violence. Therefore, the impact that exists due to the absence of changes in the behavior of the actors is the high mortality rate and the number of sexual violence that exists.